Pengaruh Dosis Pupuk NPK 16-16-16 dan Konsentrasi Pupuk Guano Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Pangestu, Abdulah Aditiya; Febria, Dila; Darma, Wika Anrya; Rahhutami, Ratih (Journal of Horticulture Production Technology, 2025)
Shallots (Allium ascalonicum L.) are horticultural crops with great potential to be developed to meet the needs and economic value of the community. Shallot production is influenced by fertilization, both inorganic and organic fertilizers. The objectives of this study were (1) to obtain the best dose of NPK fertilizer for the growth of shallots. (2) to obtain the best concentration of guano liquid organic fertilizer for the growth of shallots. (3) to obtain the best combination of NPK fertilizer doses and guano liquid organic fertilizer concentrations for the growth of shallots. This study was conducted on the horticultural experimental land of the Lampung State Polytechnic from June to August 2024. The research method used was a factorial Randomized Block Design (RAK) with 2 factors and 3 replications. The first factor used NPK fertilizer (N) with 3 levels, namely: 400 kg/ha (N1), 600 kg/ha (N2), 800 kg/ha (N3). The second factor used POC (P) with 3 levels, namely: 2 ml/L (P1), 4 ml/L (P2), 6 ml/L (P3). Each treatment was repeated 3 times so that there were 9 treatment combinations and 27 experimental units. The results showed that the application of NPK fertilizer at a dose of 600 kg/ha showed the best results for all observation parameters except plant height and number of leaves. The application of POC Guano did not show significantly different results for all observation parameters. There was no best combination between NPK fertilizer and POC Guano treatment for all observation parameters.